Interactions between polyphenol oxidation products and salivary proteins: Specific affinity of CQA dehydrodimers with cystatins and P-B peptide. (1st May 2021) - Castillo-Fraire, Claudia Mariana; Brandão, Elsa; Poupard, Pascal; Le Quére, Jean-Michel; Salas, Erika; de Freitas, Victor; Guyot, Sylvain; Soares, Susana
Highlights: Caffeoylquinic acid (CQA) oxidation products precipitate salivary proteins. Caffeoylquinic acid dehydrodimers presented a low interaction with PRPs. CQA dehydrodimers revealed specific interaction with statherins/P-B peptide and cystatins. Fluorescence quenching showed stronger interaction with cystatins compared to P-B. Abstract: Throughout the apple juice and cider making process, polyphenols undergo enzymatic oxidation which generates a great variety of polyphenol oxidation products. Since 5′-O-Caffeoylquinic acid (CQA) is one of the major phenolic compounds and the preferential substrate for polyphenoloxidase in apple juice, its oxidation leads to the formation of newly formed molecules by which dehydrodimers (MW 706 Da) are included. Interactions of salivary proteins (SP) with native polyphenols is a well-known phenomenon, but their interactions with polyphenol oxidation products has not been studied yet. In this work, we decided to decipher the interactions between CQA dehydrodimers and SP (gPRPs, aPRPs, statherins/P-B peptide, and cystatins) using HPLC-UV and fluorescence. These results showed that contrary to what was expected, CQA dehydrodimers presented a low interaction with PRPs, but revealed a specific interaction with statherins/P-B peptide and cystatins. This work settles for the first time the interactions between SP and polyphenol oxidation products.